2012
DOI: 10.1177/1462474511424684
|View full text |Cite
|
Sign up to set email alerts
|

Making the criminal addict: Subjectivity and social control in a strong-arm rehab

Abstract: The mandatory, state-subsidized treatment opened up by drug courts and other jail and prison diversion programs have massively expanded the numbers of the nation's poor and working class who are labeled addicts and sent to rehab, making drug rehabilitation a primary site for the re-socialization and control of the poor. Drawing on ethnographic and interview data, this article examines the institutional form at the center of this process: the 'strong-arm' rehabilitation facilities most closely tied to drug cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 40 publications
1
84
0
2
Order By: Relevance
“…As this case illustrates, the state sought to transform those it deemed needing reconstruction of the self, but in less expressively punitive ways than those documented in studies of court‐mandated drug treatment facilities (McKim ; Kaye ; Gowan and Whetstone ; McCorkel ) and long beyond the length of women's formal correctional sentences. Additionally, the moral foundation of the twelve‐step logic and recovery homes' faith‐based approaches drew connections between morality and sobriety.…”
Section: Interventionist Penal Controlmentioning
confidence: 99%
“…As this case illustrates, the state sought to transform those it deemed needing reconstruction of the self, but in less expressively punitive ways than those documented in studies of court‐mandated drug treatment facilities (McKim ; Kaye ; Gowan and Whetstone ; McCorkel ) and long beyond the length of women's formal correctional sentences. Additionally, the moral foundation of the twelve‐step logic and recovery homes' faith‐based approaches drew connections between morality and sobriety.…”
Section: Interventionist Penal Controlmentioning
confidence: 99%
“…Social science research has suggested that religion or state‐sanctioned faith‐based programming may deter drug use, crime, and recidivism (i.e., Dodson, Cabage, and Klenowski ; Jensen and Gibbons ; Johnson ; O'Connor and Perreyclear ; O'Connor, Ryan, and Parkikh ). However, another strand of social science has also asserted that rehabilitation socializes formerly incarcerated persons as risk‐bearing subjects (i.e., Fairbanks ; Gowan and Whetstone ; Haney ; Kaye ) and subordinates them to contingent labor markets (Haney ; Peck ; Peck and Theodore ).…”
Section: Resultsmentioning
confidence: 99%
“…The characters, narrative tropes, and treatment options depicted on Intervention sit in striking opposition to the broader social context of the criminalization of drug use by African American and Latina/o people and the disproportionate incarceration rates in the United States. In contrast, Intervention frames the characters' stories of addiction as individual ''tragedies'' rather than collective ''social problems'' associated with drug use by African Americans and Latinas/os (Gowan & Whetstone, 2012). Instead of the punitive approach meted out to drug users through government-sponsored drug wars and on shows such as Cops or Locked Up, Intervention's televisual, therapeutic approach to addiction embodies whiteness.…”
Section: Resultsmentioning
confidence: 99%